Total and regional body composition of NCAA Division I collegiate baseball athletes - Czeck, M. A.; Raymond-Pope, C. J.; Bosch, T. A.; Bach, C. W.; Oliver, J. M.; Carbuhn, A.; Stanforth, P. R.; Dengel, D. R. (International Journal of Sports Medicine, 2019)
This study`s purpose was to evaluate total, regional, and throwing versus non-throwing arm body composition measurements between various positions of NCAA Division I male baseball players using dual X-ray absorptiometry (DXA). Two hundred and one collegiate baseball athletes were measured using DXA. Visceral adipose tissue (VAT), total and regional fat mass (FM), lean mass (LM), and bone mineral density (BMD) were measured. Athletes were separated into: pitchers (n=92), catchers (n=25), outfielders (n=43), and infielders (n=41). ANOVA and Tukey`s honest significant difference assessed total and regional differences between positions. Infielders had significantly (p<0.05) lower total LM than pitchers and outfielders. Additionally, outfielders had significantly lower total FM compared to pitchers and catchers. No significant differences between positions were observed for total BMD and VAT. Pitchers` and infielders` throwing arm demonstrated significantly greater total mass, FM, LM, and BMD compared to the non-throwing arm. Further, outfielders` throwing arm total mass, LM, and BMD were significantly higher vs. the non-throwing arm. Significant differences were observed in total and regional body composition measurements across position, in addition to differences in throwing arm vs. non-throwing arm composition. These measurement values are important to coaches and trainers as normative positional DXA data for collegiate baseball players.